1984
DOI: 10.1002/bip.360230809
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational circular dichroism of polypeptides. III. Film studies of several α‐helical and β‐sheet polypeptides

Abstract: SynopsisVibrational CD (VCD) of amides A, I, and I1 vibrations of a variety of polypeptide films have been measured. VCD of films of a-helical and /%sheet structures are compared in the three regions. Reproducible spectra could only be obtained for thin films free of orientation dependence. The sign and band shape of the VCD of films are not always the same as that in solution. However, the magnitude of the observed VCD seems to correlate with the secondary structure such that a-helical molecules typically hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…Thus, both a-helix and b-sheet structures were present in B 16 D 45 B 16 , while PBGL chains of the other copolymers mainly assumed a-helix conformation. [38][39][40][41][42] The results were consistent with previous research results. 17,37 As reported in the literature, both a-helixes and b-sheets secondary structures are present in the polypeptide segments with shorter chain lengths (n < 18), whereas the b-sheets secondary structure becomes less stable in the longer polypeptides (n > 18) and the polypeptide segment almost exclusively adopts an a-helical secondary structures.…”
Section: Synthesis and Characterization Of Pblg-b-pdms-b-pblg Tribcpssupporting
confidence: 83%
See 2 more Smart Citations
“…Thus, both a-helix and b-sheet structures were present in B 16 D 45 B 16 , while PBGL chains of the other copolymers mainly assumed a-helix conformation. [38][39][40][41][42] The results were consistent with previous research results. 17,37 As reported in the literature, both a-helixes and b-sheets secondary structures are present in the polypeptide segments with shorter chain lengths (n < 18), whereas the b-sheets secondary structure becomes less stable in the longer polypeptides (n > 18) and the polypeptide segment almost exclusively adopts an a-helical secondary structures.…”
Section: Synthesis and Characterization Of Pblg-b-pdms-b-pblg Tribcpssupporting
confidence: 83%
“…3a, the signal at 1735 cm À1 was related to the C]O stretching of the benzyl ester protecting group of the PBLG block. [38][39][40][41][42] In the high resolution FTIR spectra (Fig. 3b) Scheme 1 (indicated with the arrow) was quite obvious, compared to other copolymers.…”
Section: Synthesis and Characterization Of Pblg-b-pdms-b-pblg Tribcpsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could explain why the VCD spectrum of the amide I 0 band, which probes the local environment, shows a PPII like signal. As shown by Keiderling and coworkers, 31 the observed enhancement is typical for peptide films. The effect could result from the anisotropy of the formed film and/or from interpeptide vibrational coupling between the amide I modes of adjacent PLP molecules.…”
Section: Comparison With Literaturementioning
confidence: 57%
“…22 We find that films of these polypeptides give somewhat lower-frequency amide-I bands. 17 Our results indicated that solution and film data are significantly different such that frequency shifts alone are not sufficient to determine conformation. Since only the amide N-H was deuterated, the lack of such a n effect on the PBLA spectrum may indicate that the new, resonant mode for the deuterated amide is sensitive to the conformational constraints of this left-handed L-configuration form.…”
Section: CLmentioning
confidence: 75%